Congenital Central Hypothyroidism due to a Homozygous Mutation in the TSHβ Subunit Gene - Sarah Catharina Grünert; Miriam Schmidts; Joachim Pohlenz; Matthias Volkmar Kopp; Markus Uhl; Karl Otfried Schwab (Hindawi Limited, 2011)
Congenital central hypothyroidism (CCH) is a rare condition occurring in 1 : 20000 to 1 : 50000 newborns. As TSH plasma levels are low, CCH is usually not detected by TSH-based neonatal screening for hypothyroidism, and, as a result, diagnosis is often delayed putting affected children at risk for developmental delay and growth failure. We report on a girl with isolated central hypothyroidism due to a homozygous one-base pair deletion (T313del) in exon 3 of the TSHβ subunit gene. The molecular genetic and typical radiologic findings are discussed, and a systematic diagnostic workup for congenital central hypothyroidism is proposed. Physicians need to be aware of this rare condition to avoid diagnostic delay and to install prompt replacement therapy.